Enhancing policy and strategy planning: How to tailor data visualisation and evidence sharing for improved stakeholder uptake and application - Bourne, Mieke; Neely, Constance; Magaju, Christine Lamanna; Peterson, Nathanial; Wanyama, Rosina; Vågen, Tor-G.; Chesterman, Sabrina; Winoweicki, Leigh (World Agroforestry Centre, 2021)
The CGIAR Research Program on Policies, Institutions, and Markets is seeking to provide empirical action research to support decision makers to better use evidence to support policy making and implementation, particularly timeliness and relevance with respect to policy challenges facing countries, organizations and other groups. A systemic, yet widely misunderstood and under-researched issue, is that researchers and evidence generators often do not understand how to tailor the evidence they produce to reach and influence decision makers (Winterfeldt, 2013), ensuring it is relevant and readily accessible in terms of visualization and ease of interpretation while using different approaches to increase uptake and impact through target stakeholders (Brugnach and Ingram, 2012; Harold et al., 2016; Oliver and Cairney, 2019; Tufte, 2001). The importance of sharing evidence that is salient, credible and legitimate has also been highlighted in the literature (Cash et al., 2002; Cook et al., 2013). While the field is evolving rapidly in light of, for example, big data analytics and creative visualization tools, there is a growing interest in better understanding the relationship between cognitive and emotional aspects associated with data and interpretation to prompt understanding and subsequent behavior changes in decision making, action and impact (Gibson, 2018; Winterfeldt, 2013). It is therefore important that we understand why so much research that is generated is not being used for the intended purpose by decision makers.